Are nursing students ready for robotic nurses in obstetrics and gynecologic clinics? a cross-sectional study - Kucukkaya, Burcu; Ozoglu, Merve (Bmc, 2025)
Background This study aimed to examine the relationship between nursing students' perspectives towards robotic nurses in obstetrics and gynecologic clinics, their fear of robots, their negative attitudes towards robots, and their individual innovativeness. Methods A correlational and cross-sectional research. This study was carried out between September and December 2024 by applying the Personal Data Collection Form, Individual Innovation Scale (IAS), Robot Anxiety Scale (RAS) and Negative Attitude Towards Robots Scale (NARS) to 330 students. Results There was a statistically significant negative correlation was found between the RAS and NARS total and sub-dimension mean scores (p < .001). While there was a statistically significant negative correlation between the mean scores of the IIS and the total and sub-dimensional mean scores of the RAS and NARS (p < .001), a statistically significant positive correlation was found between the mean scores of the RAS total and sub-dimensional mean scores and the mean scores of the NARS total and sub-dimensional mean scores (p < .001). It is seen that the linear regression model in which the mean total scores of the IIS, RAS and NARS were set as independent variables and the opinion on the presence of robotic nurses in the obstetrics and gynecologic clinics was set as the dependent variable was statistically significant (F = 17.141; p < .001). Conclusion As nursing students' positive views on the presence of robotic nurses in the obstetrics and gynecologic clinics increase, their sense of individual innovativeness increases and their robot anxiety and negative attitudes towards robots decrease. Providing in-service robotic nurses training can help healthcare organizations improve obstetrics and gynecologic nurses' attitudes towards robotic nurses, increase their robotic nurses literacy and reduce their anxiety.
Keywords: Individual Innovativeness; Robotic Nurse; Fear; Negative Attitudes; Nursing Student; Obstetrics And Gynecologic Clinics